Analisis Strategi Promosi dalam Upaya Peningkatan Volume Penjualan Brand Kosmetik Emina pada Toko Kosmetik Topshop 1 di Bandar Lampung - Prameswari, Puspa; Amir, Aprilianto; Susanty, Melan (Business Perspective Journal, 2023)
The object of this research is the cosmetic brand Emina which is located at the Topshop 1 Cosmetic Store in Bandar Lampung, where the two parties have worked together for a long time and are quite successful, although later the sales of Emina's cosmetic brand experienced a decline due to the pandemic that hit for approximately 2 years to the back. The purpose of this study was to determine the promotion strategy in increasing sales of the Emina cosmetic brand at the Topshop 1 cosmetic store, Bandar Lampung. The research method used is a qualitative method. Sources of data using primary data obtained through interviews. The data were processed and analyzed using descriptive qualitative analysis through deductive, inductive, and comparative methods. The results of this study show that Emina's promotional strategy, especially at the Topshop 1 cosmetics store, in increasing sales through advertising activities, personal selling followed by customer database input by BA (Beauty Advisor) which will later be followed up, as well as conducting sales promotions. through the provision of product testers, discounts, and publicity. In addition, Emina's promotions at the Topshop 1 cosmetic store are also through the use of social media. This study concludes that Emina's promotional strategy has an effect on increasing the sales volume of the cosmetic brand at Topshop 1. Keywords: analysis, strategy, promotion